Cross-crystallization method used for the crystallization and preliminary diffraction analysis of a novel di-haem cytochrome c4 - Nemčovičová, Ivana; Branca, Rui Miguel Mamede; Bodo, Gabriella; Bagyinka, Csaba; Kutá Smatanová, Ivana (Acta crystallographica. Section F, 2006)
The newly discovered di-haem cytochrome c4 from the purple sulfur photosynthetic bacterium Thiocapsa roseopersicina is the first cytochrome c4 to be crystallized from an anaerobic organism. It was crystallized using the addition of metal-ion salts to the standard vapour-diffusion method. Coloured well shaped three-dimensional crystals with dimensions of approximately 0.6 x 0.05 x 0.02 mm grew within 3-4 d at pH 5 and diffracted to 1.72 angstroms without radiation damage. Cytochrome c4 crystallized in space group P4(1)2(1)2 as a primitive tetragonal system with unit-cell parameters a = b = 75.29, c = 37.12 angstroms, alpha = beta = gamma = 90 degrees.
Keywords: Bacterial Proteins; Crystallization; krystalizace; financování organizované; Cytochrome c Group; Thiocapsa; Financing, Organized; cytochromy skupiny c; difrakce rentgenového záření; X-Ray Diffraction; bakteriální proteiny